Glucocorticoids and mineralocorticoids in hair: facilitating accurate diagnosis of adrenal-related endocrine disorders - Bianca Heyns; Rialet Pieters; Marietjie Aletta Stander; Stephen Lawrence Atkin; Amanda Cecilia Swart; Amanda Cecilia Swart (Frontiers in Endocrinology)
BackgroundGlucocorticoids and androgens in the hair follicle have been of interest for many years, particularly cortisol and cortisone in retrospective studies associated with chronic stress and Cushing’s syndrome. No studies have reported aldosterone or 18-hydroxycorticosterone in the adrenal mineralocorticoid panel in the hair follicle. This study aimed to identify potential biomarkers in endocrine conditions associated with steroid excess or deficiency using a novel extraction protocol in the analysis of mineralocorticoids and glucocorticoids in the hair follicle.Methods and findingsHair was collected from 15 healthy male and female volunteers. Segments that were cut along the length of long, medium, and short hair and segments shaved on the scalp and the cheek were prepared for analysis. Hair samples were extracted using an automated accelerated solvent extraction (ASE) system. Steroids were analyzed using high-throughput ultra-performance convergence chromatography–tandem mass spectrometry. All mineralocorticoids and glucocorticoids were detected above the lower limit of quantification and none of the steroids differed statistically comparing male and female concentrations. Deoxycortisol, deoxycorticosterone, and aldosterone were detected for the first time in men. In both genders, 18-hydroxycortisosterone was detected for the first time. The median concentrations for women and men, respectively, were as follows: deoxycortisol, 14.2 and 19.2 pg/mg; cortisol, 34.7 and 33.9 pg/mg; cortisone, 22.4 and 22.0 pg/mg; deoxycorticosterone, 83.0 and 50.2 pg/mg; corticosterone, 10.9 and 11.5 pg/mg; 18-hydroxycorticosterone, 24.8 and 24.8 pg/mg; and aldosterone, 23.4 and 22.7 pg/mg. Deoxycortisol and deoxycorticosterone showed marked fluctuation along the hair follicle in both genders and showed inter-individual variance. Conversely, cortisol, cortisone, corticosterone, 18-hydroxycortisosterone, and aldosterone did not fluctuate, with no inter-individual variance. Cortisol was 1.5-fold higher than cortisone in accordance with the circulatory cortisol/cortisone relationship.ConclusionsThe novel extraction method optimized steroid measurement, showing the consistency of measurement for glucocorticoids, cortisol and cortisone, and mineralocorticoids, corticosterone, 18-hydroxycorticosterone, and aldosterone. Data suggest these steroids in the hair follicle to be ideal biomarkers in improving diagnostic testing, investigating conditions of steroid excess or deficiency in hypoaldosteronism, primary hyperaldosteronism, Cushing’s syndrome, and the congenital adrenal hyperplasia subtypes.